(Un)Spoken realities of living with axial spondyloarthritis: a qualitative study focused on couple experiences. Issue 7 (3rd July 2019) - Raybone, Kerry; Family, Hannah; Sengupta, Raj; Jordan, Abbie
Abstract : Objective: Axial spondyloarthritis is a long-term rheumatic condition. The symptoms, including pain, can impact on the daily life routines and psychological well-being of individuals that are diagnosed with axial spondyloarthritis (axSpA). Partners are often a main source of support for individuals who manage a long-term condition and they can also be affected by the illness experience, often themselves reporting elevated levels of emotional distress. Few qualitative studies have explored the impact of axSpA on partner relationships. This study addresses the social context of axSpA by investigating the experiences for both individuals with axSpA and their partners. Design: Semistructured individual telephone interviews analysed using thematic analysis at a dyadic partner level. Setting: Participants were recruited from the social media pages of a UK-based axSpA-specific charity. Participants: Nine heterosexual partner dyads (23–65 years), who were currently cohabiting, comprising nine individuals diagnosed with axSpA (n=6 females) and nine partners (n=3 females). Results: Three themes 'Perceived relational closeness', 'Playing third wheel to axSpA' and 'Tensions surrounding a carer-type role' were identified. The findings illustrate how living with axSpA can influence closeness between partners and dominate daily decisions, particularly surrounding leisure activities. Partners commonly adopted a carer-type role, despite many individuals with axSpA expressing desire for a greater sense of autonomy. Conclusions: This study provides an important insight into the lived experiences of both individuals with axSpA and their partners. Findings highlight the social context of managing a long-term condition and suggest the need for including partners within consultations, and the need for support provision for partners.